Classroom racial/ethnic diversity and upper elementary children's social-emotional development. Issue 2 (3rd April 2021) - Rucinski, Christina L.; Sutton, Essie; Carlton, Richmond; Downer, Jason; Brown, Joshua L.
Abstract: Research has shown that racial/ethnic diversity in elementary schools and classrooms benefits children's academic achievement and feelings of safety and belonging. The current study aimed to expand on existing research by examining associations between classroom racial/ethnic composition and upper elementary children's social-emotional development and whether these associations differed based on overall quality of classroom interactions. Data were collected from 526 third- through fifth-grade children in 35 urban public elementary school classrooms. Measures included teacher-reported child social competence, teacher-child relationship quality, and aggression; child self-reported depression and anxiety; and observed classroom interactions. Hierarchical linear modeling revealed that classroom diversity was positively related to teachers' reports of child social competence and teacher-child closeness and negatively related to child-reported depression. The relationship between classroom diversity and child social-emotional development did not differ based on classroom interactional quality, indicating that these associations may be robust to differences in classroom environments.